Industrial Relations in Scandinavia - Schonning, Gil (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
The author enumerates the characteristics of the Scandinavian system of industrial relations, notes ten most significant one and compares their system with the one prevailing in Canada.